2014
DOI: 10.1016/j.psyneuen.2014.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Anger responses to psychosocial stress predict heart rate and cortisol stress responses in men but not women

Abstract: While previous research has suggested that anger and fear responses to stress are linked to distinct sympathetic nervous system (SNS) stress responses, little is known about how these emotions predict hypothalamus-pituitary-adrenal (HPA) axis reactivity. Further, earlier research primarily relied on retrospective self-report of emotion. The current study aimed at addressing both issues in male and female individuals by assessing the role of anger and fear in predicting heart rate and cortisol stress responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
34
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 44 publications
4
34
0
1
Order By: Relevance
“…Additionally, facial coding and self-report capture different components of emotion: facial coding allows for assessment of visceral, less-processed emotion experience in the moment of stress, while self-report reflects the perception of emotion after cognitive processing and self-reflection have occurred (Crockett et al, 1987). In line with this differentiation, prior research using FACS in the context of the TSST did reveal associations between anger expression and cortisol responses among men in the absence of such links for self-reported emotions (Lupis et al, 2014). Hence, although no emotion expression–cortisol relationships were discovered in the current study, future studies assessing the role of other emotions besides self-conscious emotions for cortisol stress responses may still benefit from using both methods, self-report and facial coding in conjunction.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Additionally, facial coding and self-report capture different components of emotion: facial coding allows for assessment of visceral, less-processed emotion experience in the moment of stress, while self-report reflects the perception of emotion after cognitive processing and self-reflection have occurred (Crockett et al, 1987). In line with this differentiation, prior research using FACS in the context of the TSST did reveal associations between anger expression and cortisol responses among men in the absence of such links for self-reported emotions (Lupis et al, 2014). Hence, although no emotion expression–cortisol relationships were discovered in the current study, future studies assessing the role of other emotions besides self-conscious emotions for cortisol stress responses may still benefit from using both methods, self-report and facial coding in conjunction.…”
Section: Discussionsupporting
confidence: 53%
“…While this approach increased statistical power, it may have obscured differential links between shame expressions and cortisol stress responses. The current study further focused on expressions of self-conscious emotions; however, prior studies have shown that other emotions (most notably, fear and anger) could determine strength of both SNS and HPA axis reactivity to stress, thus emphasizing the value of exploring emotion–stress links using facial coding analysis (Ekman et al, 1983; Levenson, 1992; Lupis et al, 2014; Moons et al, 2010). Together these findings suggest that future studies may benefit from assessing potential stress-relevant effects of specific emotion response patterns.…”
Section: Limitationsmentioning
confidence: 99%
“…Burn wound care [19] To examine the levels of salivary pH as a possible biomarker Salivary pH -- [8] To address both issues in male and female individuals by assessing the role of anger and fear in predicting heart rate and cortisol stress responses using both self-report and facial coding analysis to assess emotion responses.…”
Section: Cortisol Alphaamylasementioning
confidence: 99%
“…Acute stress activates a coordinated set of physiological responses (by the Sympathetic Nervous System and HPA) that prepares the body to deal with an immediate threat [7,8].…”
mentioning
confidence: 99%
See 1 more Smart Citation